MARKETING STRATEGIES IN ENHANCING COMPETITIVE ADVANTAGE - Halimatus Sa'diyah (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
This study aims to analyze the role of marketing strategies in enhancing organizational competitive advantage through a Systematic Literature Review (SLR) approach. The literature search was conducted using Scopus, Web of Science, Google Scholar, and Garuda databases, covering publications from 2011 to 2025. The SLR process involved identification, screening, eligibility assessment, and synthesis of relevant studies focusing on marketing strategies, digital marketing, and competitive advantage. The findings indicate that marketing strategies, including the marketing mix, marketing intelligence, marketing innovation, customer orientation, and digital marketing, play a significant role in creating and strengthening competitive advantage. This relationship is reinforced by supporting factors such as customer satisfaction, marketing capabilities, innovation, and organizational performance. Furthermore, the adoption of digital technologies and sustainable marketing practices contributes to long-term competitiveness, particularly for small and medium-sized enterprises. This study provides theoretical contributions to the marketing strategy literature and practical implications for organizations in designing effective and sustainable marketing strategies.